The challenge of the silver screen : an analysis of the cinematic portraits of Jesus, Rama, Buddha and Muhammad - Bakker, Freek L., 1951- (Studies in Religion and the Arts, 2009)
In 1897 - only two years after the invention of film - the first feature film about Jesus appeared. This and other films about Jesus became examples for and an inspiration for films on other important religious figures like Rama, Buddha and Muhammad. Although religious leaders did not always approve of these films, they did find a ready audience among believers. This book explores these films and looks at how these films dealt with the fundamental question of portraying an individual thought to have either divine status or a very special and unique status among human beings. This book will thus benefit not only students of religious film but also those studying the portrayal of central religious figures in the contemporary world.